American mermaid : a novel - Langbein, Julia (Art historian) (Doubleday, 2023)
"A brilliantly funny and razor-tongued debut which follows a writer lured to Los Angeles to adapt her feminist mermaid novel into a big-budget action film, who believes her heroine has come to life to take revenge for Hollywood's violations. Penelope Schleeman, a consistently broke Connecticut high school teacher, is as surprised as anyone when her sensitive debut novel, "American Mermaid"--the story of a wheelchair-bound scientist named Sylvia who discovers that her withered legs are the vestiges of a powerful tail--becomes a bestseller. Penelope soon finds herself lured to LA by promises of easy money to co-write the "American Mermaid" screenplay for a major studio with a pair of male hacks. As the studio pressures Penelope to change "American Mermaid" from the story of a fierce, androgynous eco-warrior to a teen sex object in a clam bra, strange things start to happen. Threats appear in the screenplay draft; siren calls lure people into danger. When Penelope's screenwriting partners try to kill Sylvia off entirely in a bitterly false but cinematic end, matters off the page escalate. Is Penelope losing her mind, or is Sylvia among us? American Mermaid follows a young woman braving a world of casual smiles and ruthless calculation, where she discovers a beating heart in her own fiction--a creature she'll do anything to protect. By turns both a comic and fabulously insightful tale of two female characters in search of truth, love, and self-acceptance as they move between worlds without giving up their voices"--